Religious and Emotional Communities in John Heywood and John Bale’s Interludes - Christ, Adam (Analyses/Rereadings/Theories: A Journal Devoted to Literature, Film and Theatre, 2023)
The paper examines emotional communities in early modern English drama, specifically interludes by John Heywood and John Bale. It explores the connections between emotion and religion, and seeks to uncover whether and how emotionality changes according to the politically acceptable religious doctrine – particularly in the time of Protestant reformation under Henry VIII Tudor – and how these changes are expressed in the early sixteenth century English interludes by a Catholic (Heywood) and a Protestant (Bale) author. This paper considers early modern texts of culture which have not been researched as broadly as the drama of the later English Renaissance period (such as works by William Shakespeare or Christopher Marlowe), and, drawing upon the concept of “emotional communities” introduced by Barbara Rosenwein, additionally offers insights into an ongoing discussion on emotions in history.